The impact of biological interventions on health-related quality of life in adults with Crohn's disease: a systematic review with meta-analysisResearch in context - Mirjana Stanić Benić; Vanja Giljača; Andrej Belančić; Antonia Jeličić Kadić; Vera Vlahović-Palčevski (EClinicalMedicine)
Summary: Background: Health-related quality of life (HRQoL) is one of the main issues in Crohn's disease (CD). We systematically assessed the effects of a biological treatment on HRQoL in adults with CD. Methods: We searched MEDLINE, EMBASE, and CENTRAL from inception to 26 Jul 2024 for randomised controlled trials (RCTs) investigating the effects of the biological agents approved for CD on HRQoL-related outcomes. Changes in IBDQ (Inflammatory Bowel Disease Questonnaire), SF-36 (The 36-Item Short Form Survey) and EQ-5D scores were evaluated using random-effects meta-analyses to determine if they met a clinically meaningful improvement (CMI). Cochrane's Risk of Bias tool 2 and Grading of Recommendations Assessment, Development, and Evaluation (GRADE) were applied to assess the quality and certainty of findings. PROSPERO registration: CRD42024573408. Findings: Twenty-six RCTs involving 9013 participants were included in analysis. A clinically meaningful IBDQ score improvement was observed for infliximab (mean difference (MD) of 16.09 (95% CI: −0.13 to 32.31; 4 studies; 1162 participants, very low-certainty evidence)) and upadacitinib (MD 20.65, 95% CI 7.04–34.25; I2 = 42.8%, P = 0.17; 3 studies; 1523 participants; high-certainty evidence). No significant IBDQ improvement was observed for adalimumab, certolizumab pegol, ustekinumab, or natalizumab compared to placebo (low-to high-certainty evidence). Due to considerable heterogeneity, data on vedolizumab and risankizumab could not be pooled. Interpretation: Methodological issues in HRQoL measurement, including the need for larger sample sizes, standardized reporting, and uniform participant characteristics, contribute to the low methodological quality of current evidence on the impact of biological agents on HRQoL in CD. There is a large unmet need to investigate the association between clinical outcomes and HRQoL outcomes more thoroughly. Funding: None.